Industrial Training Report: Perpustakaan Universiti Malaysia Pahang (UMP) Pekan / Siti Nur Atikah Ismail - Ismail, Siti Nur Atikah (Faculty of Information Management, 2015)
This report is made in order to fulfill the requirement in subject Industrial training (IMC 690) needed by the faculty in order to finish my degree study. This report contains all the activities, project and task done during my industrial training period from 3rd August until 31st December 2015 at the Universiti Malaysia Pahang (UMP) Library. This report also contains the information about the library and recommendation to improve the library services and facilities. All the activities and the library routine are state in the report and the attachment are at the appendix pages.